2013
DOI: 10.3758/s13415-013-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of attention and emotion: top-down attention modulates amygdala activation in psychopathy

Abstract: Psychopathic behavior has long been attributed to a fundamental deficit in fear that arises from impaired amygdala function. Growing evidence demonstrates that fear potentiated startle (FPS) and other psychopathy-related deficits are moderated by focus of attention but, to date, no work on adult psychopathy has examined attentional modulation of the amygdala, or concomitant recruitment of relevant attention-related circuitry. Consistent with previous FPS findings, here we report that psychopathy-related differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 83 publications
4
77
3
Order By: Relevance
“…The authors reported that differences in amygdala activation in subjects with psychopathy are a function of goal-directed attention (for example, focus of attention can moderate amygdala dysfunction in psychopathy). The same study reported that regions of lateral PFC (relatives to top-down attention) mediate the correlation between psychopathy and amygdala activation [44]. This can confirm the central role of top-down attention in regulating bottom-up emotion and inhibitory cues in psychopathic offenders.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The authors reported that differences in amygdala activation in subjects with psychopathy are a function of goal-directed attention (for example, focus of attention can moderate amygdala dysfunction in psychopathy). The same study reported that regions of lateral PFC (relatives to top-down attention) mediate the correlation between psychopathy and amygdala activation [44]. This can confirm the central role of top-down attention in regulating bottom-up emotion and inhibitory cues in psychopathic offenders.…”
Section: Discussionsupporting
confidence: 66%
“…Larson et al [44] conducted an fMRI study with an instructed fear task, mainly focusing on attention-related circuitry in psychopathic offenders. The authors reported that differences in amygdala activation in subjects with psychopathy are a function of goal-directed attention (for example, focus of attention can moderate amygdala dysfunction in psychopathy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may for instance speculate that the hyperconnectivity we document could reflect top‐down overregulation of BLA neurons by the frontoparietal control system, which might ostensibly deprive this system of negative affective salience (i.e., threat/punishment cues) and thus hinder optimum control of actions. Excessive frontoparietal control of BLA neurons and diminished BLA responding have been tentatively theorized in relation to impulsive and antisocial psychopathic traits [Blair, 2010; Blair, 2013b; Blair and Mitchell, 2009; Glenn et al, 2009; Larson et al, 2013; Moul et al, 2012], and subsumed to underpin the executive dysfunction and behavioral disinhibition that lie at the heart of these traits [Dolan and Anderson, 2002; Morgan and Lilienfeld, 2000; Racer et al, 2011; Sadeh and Verona, 2008; Sellbom and Verona, 2007; Zeier et al, 2012]. However, given the bidirectional flow of information between the BLA and frontoparietal structures [Barbas et al, 2003; Ghashghaei and Barbas, 2002; Sah et al, 2003; Selemon and Goldmanrakic, 1988], our finding may also reflect exaggerated bottom‐up signaling of motivational salience, potentially at the expense of negative emotional information.…”
Section: Discussionmentioning
confidence: 99%
“…While the IES model can accommodate the findings of emotional impairment, it cannot account for findings that demonstrate that redirection of attention to emotional information ameliorates the emotion impairment (Dadds, El Masry, Wimalaweera, & Guastella, 2008;Larson et al, 2013;Newman, Curtin, Bertsch, & Baskin-Sommers, 2010). …”
Section: The Integrated Emotions Systems Modelmentioning
confidence: 99%